More than just the number of denticles: morphometric and limb variability in Neotropical cladoceran Alonella dadayi (Crustacea: Cladocera: Chydoridae) - Sousa, Francisco Diogo R.; Elmoor-Loureiro, Lourdes M. A.; Maia, Sarah Souza; Panarelli, Eliana A. (Zootaxa, 2020)
The aim of this study is to describe the limb morphology of Alonella dadayi Birge (Cladocera: Chydorida) and this species’ morphometric variability regarding the carapace and postabdomen. We report for the first time a population whose individuals do not have denticles on the posteroventral corner of the carapace. Although we have observed intra- and interpopulation variability of the limbs (especially the proportion of Inner Distal Lobe setae), Alonella dadayi can also be differentiated from closely related species by the morphology of the exopodite of the second limb. The morphometric analyses show high variability in the shape of the carapace, when regarding the ventral margin and posterodorsal corner. In the postabdomen, we observed a significant variation in the preanal, anal and postanal margins. Keeping in mind the wide range of the geographic distribution of Alonella dadayi and its high morphological variability, it is possible that this taxon comprises a species complex. Such a chance needs to be tested in future studies.